A Lithium Oxythioborosilicate Solid Electrolyte Glass with Superionic Conductivity. Issue 8 (29th January 2020) - Kaup, Kavish; Bazak, J. David; Vajargah, Shahrzad Hosseini; Wu, Xiaohan; Kulisch, Joern; Goward, Gillian R.; Nazar, Linda F.
Abstract: As potential next‐generation energy storage devices, solid‐state lithium batteries require highly functional solid state electrolytes. Recent research is primarily focused on crystalline materials, while amorphous materials offer advantages by eliminating problematic grain boundaries that can limit ion transport and trigger dendritic growth at the Li anode. However, simultaneously achieving high conductivity and stability in glasses is a challenge. New quaternary superionic lithium oxythioborate glasses are reported that exhibit high ion conductivity up to 2 mS cm −1 despite relatively high oxygen: sulfur ratios of more than 1:2, that exhibit greatly reduced H2 S evolution upon exposure to air compared to Li7 P3 S11 . These monolithic glasses are prepared from vitreous melts without ball‐milling and exhibit no discernable XRD pattern. Solid‐state NMR studies elucidate the structural entities that comprise the local glass structure which dictates fast ion conduction. Stripping/plating onto lithium metal results in very low polarization at a current density of 0.1 mA cm −2 over repeated cycling. Evaluation of the optimal glass composition as an electrolyte in an all‐solid‐state battery shows it exhibits excellent cycling stability and maintains near theoretical capacity for over 130 cycles at room temperature with Coulombic efficiency close to 99.9%, opening up new avenues of exploration for these quaternary compositions. Abstract : Superionic lithium oxythioborosilicate glasses with ionic conductivities up to 2 mS cm −1 are reported with high oxygen:sulfur ratios that greatly reduce H2 S evolution upon exposure to ambient air. Solid‐state NMR studies elucidate the structural entities comprising the unique local glass structure that dictates fast ion conduction. An all‐solid‐state battery utilizing the glass as an electrolyte exhibits excellent cycling performance at 25 °C.